Pengaruh Metode Phonics Terhadap Kemampuan Membaca Bahasa Inggris Siswa Tk B Penguin Family Islamic School Bekasi - Zaitun, Siti (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2023)
The purpose of this study was to determine the effect of the Phonics learning method on students' English vocabulary reading abilities. In this quantitative study, the authors collected the necessary data through the experimental method by dividing classes into two equal grades. Then set one class as the experimental class and another as the control class. After being given treatment in the experimental class, the writer gave 5 English vocabulary readings to both classes to find out the effect of the Phonics method on the English reading skills of Kindergarten B students at Penguin Family Islamic School Bekasi. In analyzing the data, the authors found that the results of the English reading test for TK B students at Penguin Family Islamic School (X1) obtained mean = 77.25, median = 75.5, mode = 92.5, standard deviation = 14.04 and variance = 197,11. Meanwhile (X2) obtains mean = 63.67, median = 66.5, mode = 68.78, standard deviation = 15.05, and variance = 226.51. And obtaining a tcount of 2.29 with dk (24-2 = 22) with a significance level of α = 0.05 obtained a ttable of 1.717. Then tcount> ttable or 2.29 > 1.717, which means that H0 is rejected and H1 is accepted. Therefore the authors conclude that "There is an Influence of the Phonics Method on the English Reading Ability of Kindergarten B Students at Penguin Family Islamic School Bekasi".